The Development of LED-Based Dental Light Using a Multiplanar Reflector Design - Chi-Chang Hsieh; Yan-Huei Li (International Journal of Photoenergy)
A multiplanar reflector was designed to enhance the application efficiency of light-emitting diode (LED) light sources that can be employed as LED-based dental lights. This study used a high-power LED developed by Nichia, that is, a single LED capable of providing a total luminous flux of 120 lm, as the primarily light source to design and develop an LED-based dental light. This LED complies with the international standards and regulations stipulated in ISO 9680:2007. The light spots produced by the prototype were rectangular, with a length of 200 mm and a width of 100 mm. These light spots achieved maximum illumination of 12,000 lux. The use of LEDs can reduce energy consumption from 50 W to 3 W, providing an energy saving of more than 90%.